Dynamical analysis of hydromagnetic Brownian and thermophoresis effects of squeezing Eyring–Powell nanofluid flow with variable thermal conductivity and chemical reaction. Issue 6 (14th August 2019) - Ogunseye, Hammed Abiodun; Salawu, Sulyman Olakunle; Tijani, Yusuf Olatunji; Riliwan, Mustapha; Sibanda, Precious
Abstract : Purpose: The purpose of this paper is to investigate the dynamical behavior of heat and mass transfer of non-Newtonian nanofluid flow through parallel horizontal sheet with heat-dependent thermal conductivity and magnetic field. The effects of thermophoresis and Brownian motion on the Eyring‒Powell nanofluid heat and concentration are also considered. The flow fluid is propelled by squeezing force and constant pressure gradient. The hydromagnetic fluid is induced by periodic time variations. Design/methodology/approach: The dimensionless momentum, energy and species balance equations are solved by the spectral local linearization method that is employed to numerically integrate the coupled non-linear diﬀerential equations. Findings: The response of the fluid flow, temperature and concentration to variational increase in the values of the parameters is graphically presented and discussed accordingly. Originality/value: The validity of the method used was checked by comparing it with previous related article.